P671 Occurrence and clinical impact of eosinophilic esophagitis in a large cohort of children with Inflammatory Bowel Disease. (21st January 2022) - Aloi, M; Rossetti, D; Bucherini, S; Felici, E; Romano, C; Martinelli, M; Di Pasquale, V; Lionetti, P; Oliva, S
Abstract: Background: Scarce data have investigated the association between pediatric Inflammatory bowel disease (IBD) and Eosinophilic esophagitis (EoE). We, therefore, aimed to describe the epidemiology and a possible peculiar phenotype and natural history of such association. Methods: Case-control study based on the Italian Society for Pediatric Gastroenterology (SIGENP) national registry. All children with a concomitant diagnosis of IBD and EoE were included. Overall prevalence and incidence in 2 periods, 2009–2015 and 2016–2021, were calculated. Cases were matched with IBD only and EoE only patients in a 1:3 ratio. Phenotype and outcomes (courses of steroids, risk of complications, surgery, treatment escalation, and hospitalization) were compared between groups. Results: Eleven patient (age 11, 27 ± 2, 83, Male 91%) with EoE-IBD out of 3090 patients with IBD only were identified, resulting in a prevalence of 0, 35% and an incidence of 0, 18% for the period 2009–2015 and 0, 45% for the period 2016–2021. Treatment escalation rates were significantly higher in patients with IBD compared to EoE-IBD at 12 and 24-month follow-up (0 vs 30%, p = 0.04 and 9% Vs 45, 5%, p = 0.03, respectively). Patients with IBD only were at a significantly higher risk of hospitalization than both EoE-IBD and EoE only patients (Log Rank p < 0.001). We found no significant differences in major outcomes related to the EoE course in EoE-IBD patients compared to EoE patients. Conclusion: Overall, the incidence and prevalence of EoE in children with IBD are low, although the incidence seems to be rising in the six years. Having an EoE appears to be associated with a milder IBD disease course while having an IBD doesn't seem to affect the natural history of EoE. More data are needed to better define the phenotype of such condition.